Production and properties of thermostable proteases from bacillus thermoleovorans strain HSR - Tokajian, Sima (2000)
The thermophilic bacterium Bacillus thermoleovorans strain HSR secretes thermostable extracellular proteases when cultivated in the presence of tryptone. The proteases which are found to be of the metallo-protease type, showed maximal activity when incubated at 80°C and pH 7.0. The enzymes are thermostable at temperatures between 60 and 80°C in the absence of substrate. Calcium is not required for thermostability. Cu2+, Hg2+ and EDTA inhibit the protease activity while Fe2+ and Fe3+ ions enhanced the activity. SDS-PAGE studies indicate the presence of multiple protease activity bands with molecular masses between 40 and 57 kDa. The proteases show higher activity towards short synthetic peptides while a decrease in specificity was observed with longer peptides.